THE WAYS OF BASIC KNOWLEDGE INTEGRATION AND FORMATION OF CLINICAL THINKING STUDENTS IN LEARNING AT THE DEPARTMENT OF THERAPEUTIC DENTISTRY - Каюкова, В.Д. (World of Medicine and Biology, 2015)
The paper is dedicated to theoretical knowledge integration students into their clinical practice in learning at the department of therapeutic dentistry. It is necessary to finding new teaching methods, which allow to assess the level of knowledge of students, as well as to denote of clear criteria that determine the level of theoretical competence of the student and allowed to develop the skills of clinical thinking. The aim of this job where finding the ways of formation and evaluation of clinical thinking dental students during passing by them different thematic modules at the therapeutic dentistry department. It was prepared the list of theoretical-clinical tasks, examples of which described at this article. They are dedicated to structure and pathology of periodontium. Such of tasks allow quite effectively provide theoretical knowledges into the clinical education of students.
Keywords: pedagogic; clinical thinking; therapeutic dentistry; periodontium